Social validation of post-treatment outcomes of adults who stutter who participated in CARE Model treatment: replication and extension - Coalson, Geoffrey A.; Byrd, Courtney T. (Frontiers in Rehabilitation Sciences, 2025)
PurposeSocial validation provides external validity of treatment outcomes from the perspective of untrained observers. To date, clinical efficacy studies of the Blank Center CARE™ Model indicate post-treatment gains in communication competence from the perspective of participants and clinicians. A preliminary social validation study corroborated these positive treatment outcomes with ratings from the general public for a single participant in a single context. The present study was designed to replicate and extend these findings by assessing clinical outcomes from the perspective of untrained observers across multiple participants and contexts.MethodTen adults who stutter provided communication samples one week before and after completing the Blank Center CARE Model treatment. A total of 1,110 untrained observers were recruited. Each untrained observer rated only one participant at one timepoint (pre-treatment or post-treatment) in one context (dyad or presentation), and each participant was asked to provide only one rating (communication competence or stuttering severity).ResultsA significant interaction indicated that post-treatment gains were observed for communication competence, but not stuttering severity, for both contexts.ConclusionsPresent findings provide further social validation of the Blank Center CARE Model of treatment. Untrained observers confirmed that participation in this strengths-based approach significantly enhances communication competence. Notably, these changes were observed regardless of pre- to post-treatment stuttering severity, lending additional support to the premise that changes in communication and fluency are independent constructs.